Social Psychological Characteristics of Leadership in Management (Zien Journal of Social Sciences and Humanities, 2022)
This article analyzes the problems encountered in the psychology of leadership today and their solutions, the social psychological characteristics of leadership, the leader's methods and obligations, and such concepts as leadership skills.